2012
DOI: 10.1590/s0104-11692012000300011
|View full text |Cite
|
Sign up to set email alerts
|

Validation of defining characteristics for the nursing diagnosis of fatigue in oncological patients

Abstract: The objective of this study was to validate the defining characteristics for the nursing diagnosis of Fatigue in adult oncological patients. It is a cross-sectional, descriptive study with a quantitative perspective, and its type is diagnostic content validation. Data collection was carried out in a University Hospital. The sample was made up of 35 expert nurses. The instrument used was subdivided into four parts. The data was analyzed by descriptive statistics. 15 defining characteristics were identified, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…The literature shows that women with breast cancer undergoing chemotherapy present a higher rate of depression ( 12 ) . The factors contributing to depression include sleep disorders, menopausal symptoms, nausea, and pain caused by the high levels of proinflammatory cytokines, due to the tissue damage that results from chemotherapy and radiotherapy ( 13 ) . It is important to keep in mind that the rapid decrease of estrogen during chemotherapy also favors depressive symptomatology, because this hormone increases the brain's sensitivity to serotonin ( 14 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The literature shows that women with breast cancer undergoing chemotherapy present a higher rate of depression ( 12 ) . The factors contributing to depression include sleep disorders, menopausal symptoms, nausea, and pain caused by the high levels of proinflammatory cytokines, due to the tissue damage that results from chemotherapy and radiotherapy ( 13 ) . It is important to keep in mind that the rapid decrease of estrogen during chemotherapy also favors depressive symptomatology, because this hormone increases the brain's sensitivity to serotonin ( 14 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Some validation studies of the NOC have been conducted. The method proposed by Fehring () is still widely used to validate NANDA‐I content (Silva, ), and was adapted to interventions (Bavaresco & Lucena, ) and NOCs (Seganfredo & Almeida, ) since these variables do not have a specific method of validation. Currently, it is observed that diagnoses, interventions, and NOCs have been also validated by the process of consensus between experts (Azzolin et al., ; Carlson, ; Lunney, McGuire, Endozo, & McIntosh‐Waddy, ; Minthorn & Lunney, ).…”
mentioning
confidence: 99%
“…(7,8) Professionals that obtained a minimum score of five points were included in the final assessment criteria, in order to include clinical nurses who provide care to adult cancer patients in palliative care in oncology and who have knowledge of NANDA-I taxonomy and researchers in the areas of oncology, palliative care, NP and/or ND.…”
Section: Methodsmentioning
confidence: 99%